China and the West Reconsidering Chinese Reverse Glass Painting - Ambrosio, Elisa; Giese, Francine; Martimyanova, Alina; Thomsen, Hans Bjarne (Arts du verre / Glass Art / Glaskunst, 2022)
For the first time, an edited volume presents a major survey dedicated to Chinese reverse glass painting, tracing its history, its local and global diffusion, and its artistic and technical characteristics. Manufactured for export to Europe as well as for local consumption within China, the fragile artworks constitute a paramount part of Chinese visual culture and attest to the intensive cultural and artistic exchange between China and the West.